IDENTIFIKASI RISIKO PADA PROYEK WASTE TO ENERGY MELALUI KERJASAMA PEMERINTAH DENGAN BADAN USAHA DI SUMATERA BARAT - Sesmiwati Sesmiwati; Wahyudi Putra Utama; Martalius Peli (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2022)
Waste to energy (WTE) project is a solution to solve energy crisis and at the same time may resolve the waste problem. Public private partnership (PPP) scheme has been widely used to deliver WTE project. The success of PPP projects heavily relies on the advisability of management and risk sharing. Â Risk management needed to conduct in order to understand specific risks, examine risk sharing between government and public sector and analyze risk mitigation for preventing and rectifying the impact.Â The effective decision on risk needed to improve decision-making process that may occur in the WTE projects. Therefore, this study identify risk probability in PPP WTE projects in West Sumatera. This probability relying on expert judgement were collected via an empirical questionnaire survey. The respondents were invited to rate a total of 21 risk factors that impact the success of PPP WTE projects as gleaned from previous research. The overall result ranked risk probability factors that land acquisition and administration approval risk, public opposition, construction cost overrun, operating cost overrun, and design/construction/commissioning performance risk are the top five risk factors affecting the sustainable development of PPP WTE Projects. A better understanding of the risk may improve project feasibility and attract private sector for investing in WTE projects.